An Exploratory Study for Analyzing the Energy Savings Obtainable by Reshaping Processes of Sheet Metal Based Components. (2017) - Ingarao, Giuseppe; Di Lorenzo, Rosa; Fratini, Livan
Abstract: Producing materials causes about 25% of all anthropogenic CO2 emissions. Reshaping could be one of the most efficient strategy to foster material reuse and lower the environmental impact due to material production. Sheet metal forming processes can be applied to reshape sheet metal based component. This research field is still almost unexplored and the actual environmental impact saving potential has not been quantified. The present paper aims at starting to cover this research gap, a modeling effort to quantify the environmental impact saving of reshaping is proposed. Primary energy demand for conventional recycling and reshaping are quantified and compared. Primary energy savings obtainable for an aluminum hood reshaping for different production scenarios are quantified. Results reveals that reshaping could lead to significant energy saving with respect to conventional recycling route based on remelting. The present research is a first step to explore advantages and disadvantages of reshaping processes and to understand actual applicability of such a material reuse approach.